Biomarkers: diagnosis and risk assessment in sepsis - Ventetuolo, Corey E; Levy, Mitchell M (Clinics in chest medicine, 2008)
Prompt diagnosis, intervention, and risk assessment are critical in caring for septic patient but remain difficult with currently available methods. Biomarkers may become useful adjuncts to clinicians and ultimately serve as targets for future therapeutic trials in sepsis. The most relevant markers are reviewed in this article, including interleukin-6, C-reactive protein, procalcitonin, triggering receptor expressed on myeloid cells-1, and biomarker panels.